Dynamics of the Gut Bacteriome During a Laboratory Adaptation Process of the Mediterranean Fruit Fly, Ceratitis capitata - Bel Mokhtar, Naima; Catalá-Oltra, Marta; Stathopoulou, Panagiota; Asimakis, Elias; Remmal, Imane; Remmas, Nikolaos; Maurady, Amal; Britel, Mohammed Reda; García de Oteyza, Jaime; Tsiamis, George; Dembilio, Óscar (Frontiers in Microbiology, 2022)
Laboratory adaptation process used in Sterile Insect Technique (SIT) programs can exert a significant impact on the insect-gut microbiome relationship, which may negatively impact the fly’s quality and performance. In the present work, changes in the guts microbiota that occur through domestication of two Ceratitis capitata populations were investigated: Vienna8 Genetic Sexing Strain (GSS), a long-established control line and a wild population recently introduced to laboratory conditions. The bacterial profiles were studied for both strains using amplicon sequencing of the 16S rRNA V3-V4 hypervariable region in larvae and gastrointestinal tract of teneral (1 day) and adults (5 and 15 days) reared under laboratory conditions for 14 generations (F0-F13). Findings demonstrated the development of distinct bacterial communities across the generations with differences in bacterial composition, suggesting strong impact of domestication on the fly bacteriome. Moreover, different bacterial profiles were observed between domesticated wild and Vienna8-GSS displaying different patterns between developmental stages. Proteobacteria mainly members of the Enterobacteriaceae family represented the major component of the bacterial community followed by Firmicutes (mainly in Vienna8-GSS adults) and Chlamydiae. The distribution of these communities is dynamic across the generations and seems to be strain- and age-specific. In the Vienna8-GSS population, Providencia exhibited high relative abundance in the first three generations and decreased significantly later, while Klebsiella was relatively stable. In the domesticated wild population, Klebsiella was dominant across most of the generations, indicating that the wild population are more resistance to artificial rearing condition compared with the Vienna8-GSS colony. Analysis of the core bacteriome revealed the presence of nine shared taxa between most of the medfly examined samples including Klebsiella, Providencia, Pantoea and Pseudomonas. In addition, the operational taxonomic unit co-occurrence and mutual exclusion networks of the wild population indicated that most of the interactions were classified as co-presence, while in the Vienna8-GSS population, the number of mutual exclusions and co-presence interactions were equally distributed. Obtained results provided a thorough study of the dynamics of gut associated bacteria during domestication of different C. capitata populations, serving as guidance for the design of domestication protocols, improving the effectiveness of artificial rearing and thereby the SIT application.